Healthy eating to maintain a healthy immune system in pandemic - Hamid Jan Jan Mohamed (Indonesian Nutrition Association, 2022)
COVID-19, caused by the coronavirus, is primarily spread during close contact such as touching and by fluid droplets produced through cough, sneeze or talk. During this pandemic, good nutrition and a healthy lifestyle is extremely important, especially in ensuring good immune defence.